Serum neurofilament light chain in FTLD: association with C9orf72, clinical phenotype, and prognosis. Issue 6 (22nd May 2020) - Cajanus, Antti; Katisko, Kasper; Kontkanen, Aleksi; Jääskeläinen, Olli; Hartikainen, Päivi; Haapasalo, Annakaisa; Herukka, Sanna‐Kaisa; Vanninen, Ritva; Solje, Eino; Hall, Anette; Remes, Anne M.
Abstract: Objective: The aim of the present study was to compare the levels of serum neurofilament light chain (sNfL) in frontotemporal lobar degeneration (FTLD) patients of different clinical subtypes (bvFTD, PPA, and FTLD‐MND) and with or without the C9orf72 repeat expansion, and to correlate sNfL levels to disease progression, assessed by the brain atrophy rate and survival time. Methods: The sNfL levels were determined from 78 FTLD patients ( C9orf72 repeat expansion carriers [ n = 26] and non‐carriers [ n = 52]) with Single Molecule Array (SIMOA). The progression of brain atrophy was evaluated using repeated T1‐weighted MRI scans and the survival time from medical records. Results: In the total FTLD cohort, sNfL levels were significantly higher in C9orf72 repeat expansion carriers compared to non‐carriers. Considering clinical phenotypes, sNfL levels were higher in the C9orf72 repeat expansion carriers than in the non‐carriers in bvFTD and PPA groups. Furthermore, sNfL levels were the highest in the FTLD‐MND group (median 105 pg/mL) and the lowest in the bvFTD group (median 27 pg/mL). Higher sNfL levels significantly correlated with frontal cortical atrophy rate and subcortical grey matter atrophy rate. The higher sNfL levels also associated with shorter survival time. Interpretation: Our results indicate that the C9orf72 repeat expansion carriers show elevated sNFL levels compared to non‐carriers and that the levels differ among different clinical phenotypes of FTLD. Higher sNfL levels correlated with a shorter survival time and cortical and subcortical atrophy rates. Thus, sNfL could prove as a potential prognostic biomarker in FTLD.